SPATIAL PATTERNING OF SURFACE LITHICS AT THE UPPER PALEOLITHIC TIKENEKTI-2 SITE IN SOUTHEASTERN KAZAKHSTAN - Kissabayev, Dauren (Nazarbayev University School of Sciences and Humanities, 2025)
This study investigates the spatial distribution and techno-typological characteristics of 555 surface lithic artifacts from the Upper Paleolithic site of Tikenekti-2 in the Ile Alatau piedmonts of the northern Tian Shan mountains, Kazakhstan. Spatial statistical analysis rejects the null hypothesis of Complete Spatial Randomness (CSR), revealing an inhomogeneous point process shaped by human activity and post-depositional dynamics. The low cortex ratio and scarcity of finished retouched tools indicate intensive lithic retouching on-site and the subsequent transport of finished tools off-site by ancient human groups. The clustering of cores and shatter at higher elevations suggests that the knapping area was situated at the top of the hill, while raw material procurement and initial reduction occurred at even higher elevations. These findings underscore the interpretive value of surface assemblages, often overlooked at stratified open-air sites. This research offers a replicable methodological framework for interpreting surface lithic assemblages at open-air archaeological sites.
Keywords: Spatial patterning; Surface lithics; Paleolithic Central Asia; Type of access: Embargo